Braed Praes in Vanuatu: Both Gifts and Commodities?. Issue 1 (March 2015) - Jolly, Margaret; Taylor, John P.; Morgain, Rachel
Abstract The debate about braed praes1 as either gift or commodity has a long and complex genealogy in foreign writings on Oceania, engaging anthropologists, Christian missionaries, policy‐makers, and feminists. Debates between ni‐Vanuatu have been equally protracted, passionate, and complicated, creating an echo chamber of resounding conversations. Such debates and political contests about bride price address deep questions about the value of a woman – as a person, a worker, sexual partner, and mother – and engage profound philosophical questions about the local traction of imported distinctions between subjects and objects, persons and things, and how indigenous categories have been transformed by the longue durée of Christian conversions and simultaneous processes of commoditisation, complicit and conflictual. How have these transformed the 'value' of woman as bride and the character and significance of braed praes? Can the entrenched binaries in such debates be eclipsed by seeing braed praes as both gift and commodity?